2001
DOI: 10.1159/000053926
|View full text |Cite
|
Sign up to set email alerts
|

Duplication Dup(1)(q32q44) Detected by Comparative Genomic Hybridization (CGH): Further Delineation of Trisomies 1q

Abstract: Partial trisomy 1q is rare and mostly the result of an abnormal segregation of parental translocation chromosomes and their homologues. Only 31 cases have been described with pure partial trisomy 1q. In the fetus presented, chromosome analysis after amniocentesis had shown an unbalanced male karyotype with an aberrant chromosome 1. A de novo terminal duplication of the long arm was suspected but could not be verified by FISH in 1994. Five years after fetal death, retrospective identification of the additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 28 publications
7
47
1
Order By: Relevance
“…Bartsch et al, 2001;Nowaczyk et al, 2003), duplications within the region 1p36.2 → 1p31 are very rarely described (Elejalde et al, 1984;Garcia-Heras et al, 1999;Warden et al, 2001;Cogulu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bartsch et al, 2001;Nowaczyk et al, 2003), duplications within the region 1p36.2 → 1p31 are very rarely described (Elejalde et al, 1984;Garcia-Heras et al, 1999;Warden et al, 2001;Cogulu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This patient has a karyotype similar to that previously described by De Brasi et al (2001) in a case with a classical phenotype of trisomy 1q42 → qter. According to Bartsch et al (2001) such rearrangements can be classified to the group IV of partial trisomy 1q carriers. Even though the clinical description revealed some common features between our case B, the five cases summarized in Bartsch et al (2001), and an additional case (Mewar et al, 1994), the case described by De Brasi et al (2001) is almost identical to our case B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, partial 1q trisomy syndrome is a rare chromosomal abnormality, and because of the differences in the extension of the duplicated 1q segment and the frequent concomitant presence of other chromosome imbalances, the patient phenotypes are quite variable, making it difficult to delineate a syndrome phenotype (Kulikowski et al, 2008). Bartsch et al (2001) performed a comparative delineation of the 1q duplication phenotype and reported that large (1q21→qter) as well as proximal (1q11/12→q22-25) and interstitial (1q25→q31-41) duplications coincided with more severe visceral malformations, reduced life expectancy and more severe mental retardation. On the other hand, terminal duplications (1q32→qter) are associated with less severe visceral malformations, longer survival, but also severe mental retardation, while small terminal duplications (1q42→qter) show mild dysmorphisms, with intellectual performance being mostly within the normal range (Bartsch et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Bartsch et al (2001) performed a comparative delineation of the 1q duplication phenotype and reported that large (1q21→qter) as well as proximal (1q11/12→q22-25) and interstitial (1q25→q31-41) duplications coincided with more severe visceral malformations, reduced life expectancy and more severe mental retardation. On the other hand, terminal duplications (1q32→qter) are associated with less severe visceral malformations, longer survival, but also severe mental retardation, while small terminal duplications (1q42→qter) show mild dysmorphisms, with intellectual performance being mostly within the normal range (Bartsch et al, 2001). Our results obtained through the use of P036 and P070 MLPA kits allow us to assume that the region involved in 1q rearrangement has a minimum size of ~2.20 Mb, which cannot be identified by cytogenetic examination with resolution (500 bands) that in theory can only detect changes ~5.0 Mb in size.…”
Section: Discussionmentioning
confidence: 99%